Statistical inference for fractional diffusion processes - Prakasa Rao, B. L. S.; ebrary, Inc. (Chichester, U.K. : John Wiley & Sons, 2010)
"Statistical Inference for Fractional Diffusion Processes looks at statistical inference for stochastic processes modeled by stochastic differential equations driven by fractional Brownian motion. Other related processes, such as sequential inference, nonparametric and non parametric inference and parametric estimation are also discussed"--
Includes bibliographical references (p. [239]-249) and index.
Electronic reproduction.
Keywords: Fractional calculus; Probabilities; Electronic books